THE PROBLEM AND REALITIES OF UTERINE LIPOLEIOMYOMA THROUGH THE PRISM OF A CLINICAL CASE - Talash, V.V.; Нromova A.M.; Prylutska, N.O.; Orlova, Yu.A.; Mitіunina N.I.; Shafarchuk, V.M. (World of Medicine and Biology, 2025)
Uterine lipoleiomyoma is a rare variant of uterine leiomyoma, which usually develops in perimenopausal women and rarely reaches large sizes. Its sonographic similarity to ovarian teratoma, leiomyoma, or sarcoma creates diagnostic problems in practical gynecology. The relevance of reporting this clinical case is determined by the extreme rarity of uterine lipoleiomyoma in women of reproductive age and the localization of its development from the cervix and uterus simultaneously. The clinical case presented in the article demonstrates an incidental finding of uterine lipoleiomyoma in a woman of reproductive age, which was mistaken for a right ovarian teratoma during ultrasound examination. The large size of the tumor, its external similarity to sarcoma, and its close attachment to the sacrouterine ligaments, parietal peritoneum, sigmoid and rectum, ureters, and iliac vessels created technical and diagnostic problems during surgery. Given the presence of a large neoplasm in the right appendage area, increased pain, positive symptoms of peritoneal irritation, and suspicion of uterine sarcoma, extirpation of the uterus with appendages was performed. The diagnosis of uterine lipoleiomyoma was verified by histological and immunohistochemical studies.